A tradução de Memórias de um Sargento de Milícias segundo o modelo comparativo e a gramática sistêmico-funcional - Silva, Roberta Rodrigues da (2014)
The objective of this research is to examine the translated novel Memoirs of a Militia Sergeant by Manuel Antônio de Almeida from Portuguese intoEnglish, to verify the nature of the changes arising from the lexical-grammatical choices in itstranslation into the English language and what the consequences of those choicesare. As aresult of a logocentric stance,both linguistically lay peopleandexperts in translation tend to considerthetranslation as a kind of text that is the exact reproduction of a text originally written in another language. Inthe nineties, the figure of subservient to the original text translator was replaced by the figure of a visible translator that manipulates the text, the creative artist mediator of languages and cultures. What changes now is that the translator is understood as someone belonging to a certain ideological, political, psychological and culturalcontext, -factors that cannot be ignored or eliminated in a translation. Related to this issue, the hypothesis of linguistic determinism can help us to understand the reasons for thedifferences that surround the categories of the experiences incorporated into the various languages. Languages differ greatly in both categories of experiences that theyexpress andin the special linguistic means they employ to represent these categories. These differences go beyond the so well-known fact that most words do not have fully equivalent translation from one language to another. Whorf wasmore interested in relating the lexicon and grammar to the worldview of a culture (theWeltanschauung). The research should answer the following questions: (a) What is the nature of the changes arising from the lexical-grammatical choices in the translation of Memoirs of a Militia Sergeantinto the English language?(b)What are the consequences of those choices? The analysis of this novel initially relies on the methodology proposed by van Leuven -Zwart (1990) and Systemic Functional Grammar, Halliday (1994) and Halliday and Matthiessen (2004).The results show thatthe nature of lexical-grammatical choices ofthe translator are influenced by the ideological and cultural contextin whichthe translator is inserted.